(untitled) (Hà Nội, 2012)
Đây là quyển sách giới thiệu đến bạn đọc những câu tục ngữ, ca dao được chọn lọc của Việt Nam
Keywords: Folk poetry, Vietnamese,Proverbs, Vietnamese,Tục ngữ Việt Nam,Ca dao Việt Nam